2017
DOI: 10.4067/s0717-75182017000100007
|View full text |Cite
|
Sign up to set email alerts
|

Exceso De Proteínas en La Pobreza: La Paradoja Del Exceso De Peso en Niños Colombianos

Abstract: INTRODUCCIÓNEl exceso de peso y la obesidad están asociados al aumento de las enfermedades crónicas, tanto de las cardiovasculares como del cáncer (1). El exceso de peso se evidencia cada vez más a edades tempranas y la edad de inicio de ésta condición es un predictor del exceso y las enfermedades crónicas en la edad adulta (1). En los países de ingreso medio y bajo las cifras de exceso de peso siguen aumentando tanto en adultos como en niños (2). En Colombia el exceso de peso en adultos es mayor en población … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Nevertheless, that survey reported that at least 36% of the Colombian population had a protein intake deficit associated with poverty [ 30 ]. A multicentric study performed from 2009 to 2011 with children between 1 and 17 years of age found total protein intake to be positively associated with wealth level and excessive protein intake to be associated with a body mass index >25 [ 31 ]. In that same study, the relative contribution (%) of total protein to total energy/day was 12.0% ± 0.11 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, that survey reported that at least 36% of the Colombian population had a protein intake deficit associated with poverty [ 30 ]. A multicentric study performed from 2009 to 2011 with children between 1 and 17 years of age found total protein intake to be positively associated with wealth level and excessive protein intake to be associated with a body mass index >25 [ 31 ]. In that same study, the relative contribution (%) of total protein to total energy/day was 12.0% ± 0.11 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the percentage of bioavailability of haem Fe is three times higher than that of non-haem Fe and, once consumed, its absorption can be increased up to four times if it is accompanied by acidic juices (52) , dietary interventions based on the consumption of red meat and eggs within a comprehensive strategy consistent with Food-Based Dietary Guidelines, which address other public health problems such as childhood obesity, should be considered (21) . Energy expenditure should be decisive in these strategies, because there is evidence of excessive protein consumption in children in Colombia (6) . In addition, red meat and eggs are part of the traditional consumption pattern, which actually protects children from excess weight in Colombia (8) .…”
Section: Discussionmentioning
confidence: 99%
“…Fe present in animal-source foods is more bioavailable because it is found in its haem version, whose absorption is up to three times higher compared with non-haem Fe (1,5) . Red meat and eggs are part of the traditional dietary pattern of the Colombian population (6–8) , and the prevalence of consumption in a month for these two items is over 90 % (9,10) . In addition, they are sources of haem Fe: 100 g of red meat and eggs have 2⋅7 and 1⋅7 mg, respectively (11) , which is equivalent to 34 and 21 % of the recommended dietary intake/d for children between 5 and 17 years of age (5) .…”
mentioning
confidence: 99%
“…Análisis no publicados basados en la ENSIN-2005, donde la fuente de datos del consumo fue un recordatorio de las últimas 24 horas mostraron ingesta de proteínas por encima de las recomendaciones poblacionales en todos los grupos etarios. Un estudio realizado en 2009 en una muestra independiente ratificó este hallazgo 22 . Explicar por qué disminuyó el consumo de alimentos, fuente de proteínas o en general de cualquier alimento del CFC aplicado, escapa al alcance del estudio.…”
Section: Cambios En La Prevalencia Y Frecuencia/día Del Consumo Usual...unclassified